The Role of Mitochondrial Biogenesis in Human Mesenchymal Stem Cell Differentiation and Acquisition of a Cardiac Phenotype - Ajmera, Arun (East Carolina University, 2013)
Introduction: With an increased understanding of myocardial infarction, human mesenchymal stem cell (hMSC) transplantation therapies have shown promising results as a possible treatment for heart failure. However, little is known about mitochondrial biogenesis for hMSCs transplanted to a cardiac microenvironment, though mitochondria are vital to cell energy production, cellular differentiation, and cell death. The purpose of this study was to investigate the role of mitochondrial biogenesis in adult hMSC differentiation and acquisition of a cardiac phenotype. Based on recent experimental evidence, we hypothesized that mitochondrial activity would be enhanced when hMSC differentiation was directed towards a cardiac-like fate. / / Methods: Two models to direct hMSC differentiation to a cardiac-like phenotype were evaluated. In Model # 1, hMSCs were co-cultured with neonatal rat cardiomyocytes for 48 hours. In Model # 2, hMSCs were treated with a combination of 3 growth factors (GF): insulin-like growth factor-1 (IGF-1), fibroblast growth factor-2 (FGF-2), and bone morphogenetic protein-2 (BMP-2) for 48 hours and 2.5 weeks. For both models qRT-PCR was performed on Mitochondrial Transcription Factor B1(TFB1M), Ubiquinol-Cytochrome C Reductase Core Protein 1(UQCRC1), Nuclear Respiratory Factor 1 (NRF-1), and Myocyte-specific Enhancer Factor 2C (MEF2C). In GF treated hMSCs, protein expression of N-cadherin and mitochondrial Electron Transport Chain (ETC) complexes II, III, IV and V were evaluated, and mitochondrial O2 consumption was assessed. / / Results: Co-cultured hMSCs showed increased mitochondrial and cardiac specific gene expression when compared to control for TFB1M, UQCRC1, and MEF2C (p?0.05). GF treated hMSCs showed increased mitochondrial gene expression of TFB1M (p<0.05), increased O2 consumption, and increased protein expression of mitochondrial ETC complex II and N-cadherin. No significant differences in cardiac specific gene expression were observed in GF treated hMSCs. / / Conclusions: Both Models # 1 and # 2 exhibited various levels of increased mitochondrial biogenesis. Results from Model # 1 hMSCs suggest increased mitochondrial gene expression in early co-cultures, specifically Complex III, may play a role in early hMSC differentiation into a cardiac-like phenotype. Results of Model # 2 hMSCs suggest enhanced mitochondrial biogenesis with GF treatment and increased culture time may lead to improved hMSC survival and proliferation to enhance cell transplantation therapies. /
Keywords: Human mesenchymal stem cells; Growth factors; Mitochondria; Biogenesis